SPRAWLING AND URBAN TRANSPORTATION SYSTEM: IMPACT IN YOGYAKARTA, INDONESIA - Maghribi, Wildan Okto Bilal; Purnomo, Eko Priyo; Malawani, Ajree D (Universitas Negeri Yogyakarta, 2021)
This article examines the sprawling and urban transportation system in Yogyakarta City. The development and Population increasing will affect the habits of the community in using private vehicles. This article uses qualitative methods and data collection techniques are through the study of literature by finding written sources. The main sources are literature books, scientific papers, national and international scientific journals related to this research. The results of this study found that the implications of the urban transportation system in Yogyakarta still could not meet the community's need for effective and efficient urban transportation, this phenomenon had an impact on urban air quality which possibly decreasing every year and the use of private vehicles that were considered more practical by the society had resulted in density traffic, the solution and improvement of the urban transportation system needs to be done to reduce the environmental impact and habitual use of private vehicles.